Chitosan films and coatings containing essential oils: The antioxidant and antimicrobial activity, and application in food systems - Yuan, Gaofeng; Chen, Xiaoe; Li, Duo (Food research international, 2016)
Chitosan edible films and coatings have shown great promise for their application in food preservation and also are promising systems to be used as essential oil (EO) carriers. This review reports the most recent and relevant studies concerning chitosan films and coatings containing EOs. The effect of EO incorporation on the antioxidant, antibacterial and antifungal activities of chitosan films and coatings in vitro and in vivo, as well as their applications in food systems have been discussed. In general, incorporation of EOs significantly increased the antioxidant, antibacterial and antifungal efficacy of chitosan films and coatings in vitro. EO-incorporated films and coatings also showed greater effectiveness against postharvest fungi and foodborne bacteria in food systems than pure films and coatings. The application of chitosan films and coatings containing EOs usually led to an extension of the shelf-life and reduction of lipid peroxidation of fish and meat products over pure chitosan films and coatings. In addition, chitosan coatings incorporated with EOs were more effective in maintaining fruit and vegetable quality, and controlling their postharvest decay during storage and shelf life than pure chitosan coatings. •Incorporation of EOs increased antioxidant and antimicrobial efficacy of chitosan films and coating.•Chitosan-EOs were more effective in extension of shelf-life and maintaining quality than chitosan.•Chitosan-EOs were more effective against pathogen and fungi in food than chitosan.